THE USE OF AUDIO VISUAL MEDIA IN TEACHING ENGLISH FOR NON-ENGLISH MAJORS - Irma Manda Negara (IKIP PGRI Pontianak, 2017)
The purpose of this study is to improve students learning outcomes through the use of audi visual media in teaching English for non-English majors. This study is an classroom action research that conducted in two cycles. The subject in this study is fourth semester students of STIE Indonesia Pontianak in academic year 2016-2017. This study uses data analysis techniques from observation and student learning outcomes. The process and the steps of research begin from planning, implementation, observations, and reflection. The results showed that lecturer activity in the cycle I reached 66.67% and cycle II reached 83.33% it means an increase of 16.66%. Likewise, students activity in the cycle I reached 73.33% and cycle II reached 90%, which means there is an increase of 16.67%. From these results indicate that the use of audio visual media in teaching English for non-english majors shows increased activity of lecturers, activities and student learning outcomes. Keywords: teaching English, audio visual media, learning outcomes.